A casemix: congestive heart failure readmission rate and its associated factors in a tertiary teaching hospital in Kuala Lumpur - Wong, CM; Abdullah Aliff AW,; Mohd Shahrol AW,; Diana Safraa Selimin,; Lavanyah S,; Hamat Hamdi Che Hassan,; Amrizal MN,; Aljunid SM,; Aniza Ismail, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2020)
Cardiovascular mortality is within the top five causes of death from non-communicable disease based on World Health Organization profile. Around 20% of heart failure patients are readmitted within 30 days worldwide. Readmission within 30 days for congestive heart failure often related to non-compliant to fluid restriction, natural progression of the disease or pre-mature discharge. The study aims to evaluate the 30 days readmission rate of congestive heart failure in Universiti Kebangsaan Malaysia Medical Centre (UKMMC) from the year 2016-2017 using casemix data and to determine the associated factors related to it. Based on the data coding, cost of readmission incurred was calculated. The 30-days readmission rate of heart failure to UKMMC in the year 2016-2017 was 53.5% & 43.5%, higher than the developed countries standard but similar to that of local teaching hospitals. After adjustment, age and level of severity are the only significant associated factors for the 30-days readmission rate. Shorter average length of stay (ALOS) & lower extra-tariff were achieved for readmission of heart failure. Total of RM80,329.73 was saved in the year 2017 from prompt treatment and comprehensive care plan of treating 19.3% level 3 severity patients at level 1 ALOS and tariff-cost. The 30-days readmission rate for heart failure in UKMMC was comparable to local teaching hospitals. The reduction of 30-days readmission rate in 2017 saved much cost, shows good clinical governance and advanced treatment strategy. Casemix can be used to guide budget allocation for the cardiology department of UKMMC.